Audit Committee, ESG Score, and Firm Value: An Information Systems Audit Perspective for Automotive Companies - Ridwan; Muchriana Muchran; Ramly; Azizah Saban (Jurnal Ilmu Manajemen Profitability, 2026)
This study investigates the effect of Environmental, Social, and Governance (ESG) scores on firm value and examines the moderating role of the audit committee from an information systems audit perspective in Indonesian automotive companies. Using an explanatory quantitative approach, this research employs firm-year secondary data from automotive sector firms listed on the Indonesia Stock Exchange over the 2021–2023 period. Firm value is measured using Tobin’s Q, ESG performance is proxied by composite ESG scores, and the audit committee is represented by its size as an internal governance mechanism. Data are analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS 27. The findings reveal that ESG scores do not have a significant effect on firm value, indicating that capital market participants have not fully internalized ESG information as a primary determinant of valuation within the Indonesian automotive sector. In contrast, the audit committee demonstrates a positive and significant effect on firm value, highlighting the importance of effective internal monitoring mechanisms in enhancing market confidence. Furthermore, the interaction between ESG scores and the audit committee is negative and statistically insignificant, suggesting that the audit committee does not strengthen the ESG–firm value relationship but functions more as a screening mechanism that ensures the credibility and reliability of ESG information produced by corporate information systems. This study contributes to the ESG and corporate governance literature by integrating an information systems audit perspective, emphasizing that ESG effectiveness as a value-relevant signal depends on the quality of internal oversight and data integrity. Practically, the findings imply that strengthening audit committees and ESG-related information systems is crucial for improving ESG credibility in emerging capital markets.